Grit As a Predictor of Academic Burnout Among University Students Writing Their Theses Under The Guidance of The Among System - Amelia Putri Arnanto; Berliana Henu Cahyani; Andreas Yudha Fery Nugroho (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
This study was carried out to obtain empirical evidence regarding the relationship between grit and academic burnout among final-year students at Universitas Sarjanawiyata Tamansiswa. The hypothesis stated that the two variables would show a negative association. The sampling process employed a nonprobability technique, specifically purposive sampling, based on criteria such as being an active UST student, currently in the final semester, and in the process of completing a thesis, with both male and female students included. The results indicated a significant negative relationship between grit and academic burnout, thereby supporting the proposed hypothesis. These findings suggest that students with higher levels of grit tend to experience lower levels of academic burnout, whereas those with lower grit are more likely to encounter higher burnout. The analysis produced a correlation coefficient of r = -0.765 with a significance value of p = 0.001 (p < 0.05), and the coefficient of determination (R Square) of 0.585 shows that grit accounts for 58.5% of the variation in academic burnout.Burnout akademik merupakan permasalahan psikologis yang banyak dialami mahasiswa tingkat akhir akibat tuntutan akademik yang berkepanjangan, khususnya dalam proses penyusunan skripsi. Penelitian ini bertujuan untuk mengetahui hubungan antara grit dan burnout akademik pada mahasiswa tingkat akhir di UST. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel penelitian dipilih menggunakan teknik nonprobability sampling dengan metode purposive sampling berdasarkan kriteria mahasiswa aktif UST, berada pada semester akhir, dan sedang menyusun skripsi, baik laki-laki maupun perempuan. Hasil analisis menunjukkan bahwa terdapat hubungan negatif yang signifikan antara grit dan burnout akademik, yang berarti hipotesis penelitian dinyatakan terbukti. Temuan ini mengindikasikan bahwa semakin tinggi tingkat grit yang dimiliki mahasiswa, semakin rendah kemungkinan mereka mengalami burnout akademik, dan sebaliknya. Nilai koefisien korelasi yang diperoleh adalah r = –0,765 dengan nilai signifikansi p = 0,001 (p < 0,05), sedangkan koefisien determinasi (R Square) sebesar 0,585 menunjukkan bahwa grit memberikan kontribusi sebesar 58,5% terhadap variasi burnout akademik.